2019
DOI: 10.1371/journal.pone.0210591
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prevalence of prehypertension and hypertension in children and adolescents in the eastern, central and western regions of China from 1991-2011 and the associated risk factors

Abstract: The present study aimed to estimate the differences in rates of prehypertension and hypertension in children and adolescents among three regions with different socioeconomic status in China, and explore the corresponding risk factors associated with prehypertension and hypertension to guide the prevention. Blood pressure measurements of 13 762 children and adolescents aged 6–17 years were obtained from a prospective national survey (the China Health and Nutrition Survey, 1991–2011). Prehypertension and hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
5
22
0
3
Order By: Relevance
“…The prevalence of high blood pressure among adolescents is increasing [3]. In our study, the prevalence of elevated BP was compatible with recent reports which grouped pre-hypertensive and hypertensive status in the analysis [25,26]; and also with the total population of ERICA study, in which 14.5% pre-hypertensive and 9.6% hypertensive adolescents were identified, aiming total prevalence of elevated BP of 24.1% [14]. Despite that, it is a not common practice to screen for hypertension among children and adolescents routinely [27].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of high blood pressure among adolescents is increasing [3]. In our study, the prevalence of elevated BP was compatible with recent reports which grouped pre-hypertensive and hypertensive status in the analysis [25,26]; and also with the total population of ERICA study, in which 14.5% pre-hypertensive and 9.6% hypertensive adolescents were identified, aiming total prevalence of elevated BP of 24.1% [14]. Despite that, it is a not common practice to screen for hypertension among children and adolescents routinely [27].…”
Section: Discussionsupporting
confidence: 92%
“…Given the modifiable risk factors of prehypertension/hypertension, the increase in prevalence is alarming. Contributing modifiable risk factors to the development of adolescent prehypertension/hypertension have been widely identified as a lack of physical exercise resulting in a high prevalence of childhood obesity (Dionne et al., 2017; Pescatello et al., 2019; Twig et al., 2016), increased sodium intake (Dionne et al., 2017; Falkner, 2015; Fan, Liao, Zong, & Zhang, 2019), and increased blood glucose measurements (Jobe, Agbla, Prentice, & Hennig, 2017; Simental‐Mendía et al., 2019; Yan et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One cross‐sectional study, based in an urban city in Iran, reported over 15% of children aged 7–17 years old as having undiagnosed prehypertension/hypertension (Badeli et al., 2016). BP measurements of children and adolescents were obtained from a National prospective survey from three regions in China and these data were used to compare the prevalence and trajectories of child and adolescent prehypertension/hypertension from 1991 to 2011; a significant increase in adolescent hypertension was found in every region (Fan et al., 2019). A recent systematic review explored the prevalence of prehypertension/hypertension in children and adolescents across the globe and found a secular increase over the last two decades (Song et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations